Sustainable energy generation from textile biowaste and its challenges: A comprehensive review - Khandaker, S.; Bashar, M.M.; Islam, A.; Hossain, M.T.; Teo, S.H.; Awual, Rabiul (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The inevitable depletion of fossil fuels has retained a growing concern among the world leaders about the future energy security. The researchers and energy experts have unequivocally agreed that bioenergy could be a sustainable solution to the impending energy crisis. Textile and apparel are the largest and oldest industry in human society. The development of textile market depends on the growth of population, economic development and rapid change of fashion. Consequently, huge amount of biowaste in the form of solid and effluent are generated from textile industries which could be potential to generate bioenergy. Although various types of feedstocks are practically being used in recent years, the generation of bioenergy from textile biowaste is comparatively unexplored area of research. This review mainly focuses the generation of bioenergy from textile biowaste which is released from different stages of textile processing as well as post-consumer garments waste. The discussion on the available treatment technologies with their merits, demerits, and production performance including key factors are highlighted. The potential of the treatment technologies dealing with the bioenergy conversion from textile biowaste are also appended.